Challenges Encountered by Teacher Trainees in Descriptive Essay Writing in English - Sathappan, Ramesh; Palpanadan, Sarala Thulasi (Development in Language Studies, 2023)
The low performance of teacher trainees in descriptive essay writing calls for a review of the approach to teaching writing. The teacher trainees faced problems in the areas of idea organization, elaboration and word choice. A lot of research has been conducted to investigate whether Process Writing has any influence on improving learners’ writing skills. However, little is known whether such a process has any influence on teacher trainees at the Malaysian Teacher Education Institutes (MTEI’s). This study, therefore, is aimed at exploring the challenges encountered by the teacher trainees in descriptive essay writing in English among teacher trainees at MTEI. This study found that the teacher trainees were not able to present their ideas coherently and clearly through participants’ behavior, generating ideas and lack of interaction. The results of the interview showed that the teacher trainees preferred the Process Approach because it provided a good discussion platform for the teacher trainees. Process Writing can be successfully implemented in schools with the cooperation of the teacher trainees and the school administration. Further research could be conducted in other educational institutes to establish the outcomes of the effectiveness of the Process Approach.